Estado do conhecimento sobre a presença de mulheres nos cursos de engenharia em artigos científicos (2008-2018) - Mata, Ana Flávia Martins da (2020)
Historically, women have experienced and still experience various forms of submission and oppression in various contexts, including in labor relations, from their insertion in courses aimed at socially considered male areas, to access to the labor market and the construction of their career. This situation is also experienced by them in engineering, where the disadvantages in relation to men are manifested in the division and qualification of tasks, in the production of scientific and technological knowledge, in salaries, among others. The present work has the general objective of conducting a survey of the academic articles produced on the presence of women in engineering, between the years 2008 to 2018, in the Periodical Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES). The specific objectives are to: analyze the investigative trends of the themes; identify the convergences and divergences of the research methodologies; identify the objectives outlined in the research; identify the results and conclusions obtained. It is a qualitative research, of the state of knowledge type, of bibliographic character, which seeks to answer the following question: What was theoretically produced in scientific articles in the period between 2008 and 2018, about the presence of women in Brazilian engineering? The first chapter discusses the relationship between gender and the world of work. The second chapter traces a brief history of the emergence of Engineering and discusses the insertion of women in this area. In the third chapter, the articles that address the theme of women in engineering are presented, published on the CAPES Journal Portal and the analysis and discussion of these articles is carried out. The articles published in the surveyed period pointed out serious discriminatory barriers experienced by women when they entered the engineering fields and signaled some possible ways out to face this issue, such as the organization of collective movements involving the entire university community and also the deconstruction of gender stereotypes throughout education basic. However, little was said about the importance of rethinking the curriculum of engineering courses and the training of teachers to work in these spaces, taking into account the discussions about gender issues.